f(x) + n - translate the graph of f(x) n units up
f(x) - n - translate the graph of f(x) n units down
f(x + n) - translate the graph of f(x) n units left
f(x - n) - translate the graph of f(x) n units right
---------------------------------------------------------------------------------------
f(x) = |x - 2| + 3
g(x) = |x| → f(x - 2) + 3 = |x - 2| + 3
Translate the graph of g(x) 2 units right and 3 units up.
g(x) = |x|
for x = -2 → y = |-2| = 2 → (-2, 2)
for x = 0 → y = |0| = 0 → (0, 0)
for x = 2 → y = |2| = 2 → (2, 2)